Supporting the social inclusion of children and young adults with IDD and psychiatric comorbidities: Autobiographical narratives of practitioners and academics from Europe - Boyle, Andrew; Abdulla, Sam; Odrowąż-Coates, Anna; Tah, Jude; Kiss, Julien; Grung , Rolf Magnus; Ahlström, Margareta; Marsh, Lynne (Society Register, 2023)
The article provides a reflection on the social inclusion of children and young people with IDD and associated psychiatric comorbidity through the eyes of practitioners and academics from Norway, Scotland, Sweden, and Romania. Using an autoethnographic approach to share the first-hand experiences of supporting children and young adults with IDD from the perspective of experienced practitioners, telling their stories (individual case studies) and mapping the challenges and successes (best practice) through these professional narratives. The article also acknowledges psychiatric comorbidity in young people with IDD and how psychiatric disorders can impact social inclusion. The results of the self-reflection of active practitioners involved with complex disabilities may serve as a guide for others in sharing best practices and facing difficulties. It also shows the policy developments on a timeline of their practice. Practice-informed issues clinicians and support staff face may aid the training and share the knowledge with other experts. The value added is the interprofessional exchange created by the international contributors.